Structural Characterization of the Tn7 Target Selection Protein TnsE - Caron, Jeremy (My University, 2017)
Tn7 and Tn7-like transposons are complex elements found in disparate environments and are responsible for mobilizing a wide variety of genes and forming pathogenicity/fitness islands. They are novel in their ability to recognize both a single site in the chromosome and specifically target transposition into mobile plasmids via dedicated TnsD and TnsE targeting proteins. TnsE recognizes mobile plasmids through an association with the processivity clamp and a 3′ recessed DNA end during conjugal replication. However, the mechanism for the specific recognition of 3′ recessed DNA ends remains unclear. Structural analyses of the C-terminal domain of TnsE identified a novel protein fold including a central V-shaped loop that toggles between two distinct conformations. The structure of a robust TnsE gain-of-function variant has this loop locked in a single conformation, suggesting that conformational flexibility regulates TnsE activity. Structure-based analysis of a series of TnsE variants relates transposition to DNA binding stability. Follow up studies of full length TnsE bound to DNA are in progress.
Keywords: Bacterial Transposition; Transposase; DNA-Binding Protein; Protein Structure; Tn7; TnsE; Transposon Targeting